Corrosion law of cement paste under hydrogen sulfide conditions in natural gas wells - She, Chaoyi; Zheng, Youzhi; Chen, Lili; Fan, Yu; Yang, Jian; Cai, Jingxuan (Frontiers in Materials, 2023)
Abstract：Downhole anticorrosion in sour gas (H2S or CO2) wells is one of the technical problems in the petroleum engineering and the corrosion raw of the cement paste, which is the "first barrier of the wellbore", need to be focused on. Aiming at the problems existing in the current research on the corrosion of the underground cement paste, a curing method for interfacial corrosion is proposed. And X-ray diffraction and scanning electron microscopy are used to investigate the corrosion mechanism of cement paste cured under hydrogen sulfide (H2S) conditions in natural gas wells. Experimental results show that the corrosion depth of cement paste is proportional to the partial pressure of H2S and the corrosion time, the compressive strength of cement paste after corrosion is inversely proportional to the H2S partial pressure value and the corrosion time. Due to the gradual enrichment, accumulation and migration of products after the cement paste is corroded by H2S, the cement paste forms a relatively stable dense layer or corrosion transition zone, the porosity and permeability of cement paste after corrosion increased with corrosion time, showing the characteristics of first increase and then decrease and finally make it more difficult for the corrosive medium to enter the interior of the cement paste. It is an important method stable corrosion transition zone forms as soon as possible, which is important to maintain the long-term sealing and chemical integrity of the cement-sheath in natural gas wells containing H2S.